Property rights and climate migration: Adaptive governance in the South Pacific. Issue 2 (20th October 2020) - Fitzpatrick, Daniel; Monson, Rebecca
Abstract: How would a polycentric property system react to mass movements of people caused by escalating climate change? Drawing on multidisciplinary perspectives, the article suggests an analytical frame for polycentric property system responses to climate migration. The case study is Solomon Islands, a South Pacific state with high levels of environmental vulnerability, where people draw on various governance mechanisms to secure proprietary relationships with land. These governance mechanisms not only encompass property rights derived from the state, but also proprietary relationships secured through social norms, informal agreements, and acts of mutual coordination. The key argument is that governance mechanisms to secure property rights for climate migrants have absorptive limits that affect broader processes of adaptation to climate change. The heuristic of absorptive capacity provides a basis to consider adaptive property law for a future of climate migration.